Irrigação na produção de silagem de milho e sorgo, em sucessão ao arroz de terras altas - Spohr, Renato B.; Maggi, Marcio F. [UNESP]; Carlesso, Reimar; Kunz, Jefferson H.; Fiorin, Tatiana T. (Departamento de Engenharia Agrícola - UFCG, 2005)
The objective of this work was to evaluate different sowing dates to maximize double-cropping (upland rice followed by either maize or sorghum) and evaluate the economica practicability of this production system in the region of Santa Maria, in the State of Rio Grande do Sul. Two experiments were conducted in the experimental field of the Agricultural Engineering Department of the Federal University of Santa Maria - RS, Brazil, during the 2001/2002 growing season. A randomized block design was used with four replications. Treatments of the first experiment were constituted of four sowing dates of upland rice: September 18, October 4, October 19 and November 5. The treatments of the second experiment were constituted of four sowing dates of maize and sorghum (after the harvest of the upland rice): January 28, February 8, February 20 and March 5. The upland rice sowing dates caused differences in grain yield and the maximum technical efficiency (5.80 Mg ha-1) was observed for the rice sown on October 13. The use of double-cropping cultivation in the southern half of Rio Grande do Sul the State upland rice followed by sorghum for the production of silage, for maximum retnans, the upland rice should be sown during de second half of September.

Tendo em vista o propósito de se avaliar épocas de semeadura para maximizar a produção de arroz de terras altas e de milho e sorgo em sucessão e avaliar o retorno econômico desse sistema de produção irrigado, na região de Santa Maria, RS, conduziu-se este trabalho em área experimental do Departamento de Engenharia Rural da Universidade Federal de Santa Maria, no ano agrícola 2001/2002. Conduziu-se dois experimentos em delineamento experimental de blocos ao caso, com quatro repetições. O primeiro experimento constituiu-se de quatro datas de semeadura do arroz (18 de setembro, 4 de outubro, 19 de outubro e 5 de novembro); no segundo experimento foram utilizadas as seguintes datas de semeadura do milho e do sorgo, semeados após a colheita do arroz, em 28 de janeiro, 8 de fevereiro, 20 de fevereiro e 5 de março. As datas de semeadura do arroz ocasionaram diferenças no rendimento de grãos, apresentando a máxima eficiência técnica (5,80 Mg ha-1) na semeadura estimada de 13 de outubro. Na sucessão de culturas irrigadas de arroz de terras altas para produção de grãos e sorgo para produção de silagem, a maior receita líquida foi observada com a semeadura do arroz, na segunda quinzena de setembro.
Production of maize and sorghum for silage in succession to the upland rice
Keywords: crop rotation; agricultural zoning; dry matter; rotação de culturas; zoneamento agrícola; massa seca